Gender equality: latest perspectives in the field of reconciliation, gender violence and asylum - Saura Freixes, Nuria (2025)
The gender perspective considered transversally is considered in this study around three crucial aspects: the reconciliation of family life and professional life of parents and caregivers; domestic violence, gender-based violence and violence against women and gender-based asylum. In such a way that the latest developments and controversies are analyzed from an analysis of the recent changes introduced at the European level considering the care measures, the construction of the offenses in the new Directive (EU) 2024/1385 of the European Parliament and of the Council of 14 May 2024 on combating violence against women and domestic violence, as well as the need for an introduction of gender-based persecution in the new Regulation 2024/1347 for the recognition of third-country nationals or stateless persons as beneficiaries of international protection, to a uniform status for refugees or for persons eligible for subsidiary protection and to the content of the protection granted, and amending Council Directive 2003/109/EC and repealing Directive 2011/95/EU of the European Parliament and of the Council.